MAKNA ŪLŪ AL-ALBĀB DALAM AL-QUR’AN: Analisis Semantik Toshihiko Izutsu - Zulfikar, Eko (Jurnal THEOLOGIA, 2018)
Abstract: One of the words of the Qurâ€™an which shows the meaning of the one who possesses knowledge is Å«lÅ« al-albÄb. ÅªlÅ« al-albÄb is the 16 terms mentioned in 10 letters in the Qurâ€™an. Every verse contained in various letters certainly has a different meaning, so it requires a deep understanding. Disclosure of the meaning Å«lÅ« al-albÄb will be analyzed by the author by using semantic al-Qur'an developed by Toshihiko Izutsu. The semantic of the Qurâ€™an according to Izutsu is an attempt to expose the worldview of the Qurâ€™an (weltanschauung) through semantic analysis of the vocabulary or key terms of the Qurâ€™an. The process undertaken in this study is to examine the basic meaning and relational meaning of Å«lÅ« al-albÄb by using syntagmatic and paradigmatic analysis, then to examine the use of vocabulary Å«lÅ« al-albÄb in pre-Qurâ€™anic, Qurâ€™anic and post-Qurâ€™anic.Abstrak: Salah satu kata al-Qurâ€™an yang menunjukkan makna orang yang memiliki akal pengetahuan adalah Å«lÅ« al-albÄb. ÅªlÅ« al-albÄb merupakan istilah yang disebutkan sebanyak 16 kali yang terliput dalam 10 surah di dalam al-Qurâ€™an. Di setiap ayat yang terdapat di berbagai surah tentunya memiliki makna yang berbeda, sehingga membutuhkan pemahaman yang mendalam. PengÂungkapan makna Å«lÅ« al-albÄb tersebut akan penulis analisa dengan mengÂgunakan semantik al-Qurâ€™an yang dikembangkan oleh Toshihiko Izutsu. Semantik al-Qurâ€™an menurut Izutsu merupakan sebuah usaha menyingkap pandangan dunia al-Qurâ€™an (weltanschauung) melalui analisis semantik terhadap kosakata atau istilah-istilah kunci al-Qurâ€™an. Proses yang dilakukan dalam penelitian ini adalah meneliti makna dasar dan makna relasional kata Å«lÅ« al-albÄb dengan menggunakan analisis sintagmatik dan paradigmatik, kemudian meneliti penggunaan kosakata Å«lÅ« al-albÄb pada masa pra-Qurâ€™anik, Qurâ€™anik dan pasca-Qurâ€™anik.